Romanov i Krım : Ekaterina II, Aleksandr I, Nikolay I, Aleksandr II, Aleksandr III, Nikolay II = The Romanovs and the Crimea : Catherina II, Alexander I, Nicholas I, Alexander II, Alexander III, Nicholas II (Moskva)
167 s.